Antibiotic therapy in atopic dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The pathogenetic role of Staphylococcus aureus (S.a.) in atopic dermatitis (AD) and the therapeutic implications related with this infectious agent are matters particularly debated by the experts. Some Authors support the idea that S.a. has a fundamental relevance in the evolution of the disease and consequently they are in favour of an antiseptic treatment of this condition. Another group of experts consider S.a. a secondary host and support the view that its penetration is caused by alterations of the barrier properties of skin. They also suggest that this agent may cause complications only in a small percentage of AD subjects. This argument has theoretical and practical implications which will be discussed in this article.